Photodegradation of methylene blue by mechanosynthesized BiFeO3 submicron particles. (3rd October 2018) - Volnistem, E. A.; Bini, R. D.; Dias, G. S.; Cótica, L. F.; Santos, I. A.
Abstract: In this paper, the photocatalytic activity of bismuth ferrite particles synthesized by high-energy ball milling is evaluated by considering the degradation of methylene blue solutions. Once chemical routes are extensively used to produce these kind of photocatalytic reactors, this mechanochemical route has the advantage of large-scale and low-cost production. The structural, microstructural and optical properties of bismuth ferrite powders are investigated and the photocatalytic efficiency is experimentally proved. The results show a degradation of 95% of the methylene blue dye, which became complete after the addition of the H2 O2 oxidizing agent and 15 min of illumination.